feasibility study ANALISA KELAYAKAN USAHA PETERNAKAN AYAM LAYER PASCA PANDEMI COVID-19 DI CV. PUTRA PRATAMA: Analisa Ekonomi - Zia Fithron; Ahmad Khoirul Umam; Hanum Muarifah; Nanang Febrianto (LPPM UNIVERSITAS KAHURIPAN KEDIRI, 2022)
This research was conducted at CV. Putra Pratama. The purpose of this study was to find out how much profit and business feasibility on layer farms after the Covid-19 pandemic. The method used is a case study method on layer chicken farming, this method is done by collecting data systematically. The result of this research showed that the average price of eggs for a month was Rp. 21,500/kg, and the total cost was Rp. 2.879.039.049,-. Total revenue was Rp. 2.815.323.665,. The analysis of break event point was reached Rp. 24.960/kg and the result of revenue of cost ratio was 0,97. These criteria are still feasible to continue despite experiencing losses, because the economy in Indonesia after Covid-19 is moving productively.